2022
DOI: 10.3390/ma15238693
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufactured Magnesium-Based Scaffolds for Tissue Engineering

Abstract: Additive manufacturing (AM) is an important technology that led to a high evolution in the manufacture of personalized implants adapted to the anatomical requirements of patients. Due to a worldwide graft shortage, synthetic scaffolds must be developed. Regarding this aspect, biodegradable materials such as magnesium and its alloys are a possible solution because the second surgery for implant removal is eliminated. Magnesium (Mg) exhibits mechanical properties, which are similar to human bone, biodegradabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 158 publications
0
19
0
Order By: Relevance
“…Using 3D-printed magnesium composite scaffolds, which have been presented as an important approach for bone defect repair, Xu et al found that both platelet-derived growth factor BB (PDGF-BB) and BMP2 expression were upregulated, thereby displaying excellent osteogenetic, angiogenetic, and mechanical properties . Besides, the alkaline environment formed during Mg 2+ release also increases osteoblast-mediated mineral deposition and inhibits osteoclast activity, thus accelerating bone regeneration . Consequently, the oxygen and Mg 2+ released in response to MgO 2 implantation can effectively promote the subsequent bone defect repair process and play a dual synergistic role.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using 3D-printed magnesium composite scaffolds, which have been presented as an important approach for bone defect repair, Xu et al found that both platelet-derived growth factor BB (PDGF-BB) and BMP2 expression were upregulated, thereby displaying excellent osteogenetic, angiogenetic, and mechanical properties . Besides, the alkaline environment formed during Mg 2+ release also increases osteoblast-mediated mineral deposition and inhibits osteoclast activity, thus accelerating bone regeneration . Consequently, the oxygen and Mg 2+ released in response to MgO 2 implantation can effectively promote the subsequent bone defect repair process and play a dual synergistic role.…”
Section: Resultsmentioning
confidence: 99%
“…55 Besides, the alkaline environment formed during Mg 2+ release also increases osteoblast-mediated mineral deposition and inhibits osteoclast activity, thus accelerating bone regeneration. 56 Consequently, the oxygen and Mg 2+ released in response to MgO 2 implantation can effectively promote the subsequent bone defect repair process and play a dual synergistic role. In summary, 3D-printed PCL/nHA/MgO 2 (10%)/PDA scaffolds have great potential as bone grafts for promoting bone regeneration.…”
Section: In Vivo Osteogenic Performancementioning
confidence: 99%
“…Generation of precise pore sizes along with patient specific geometry is one of the major advantages of this technique. Maximum reduction of porosity between the initial CAD design and fabricated scaffold was obtained around 6.1% . Furthermore, this process allowed a 70% average increase in the surface area of the scaffold.…”
Section: Fabrication Techniques Of Mg Scaffoldsmentioning
confidence: 99%
“…Maximum reduction of porosity between the initial CAD design and fabricated scaffold was obtained around 6.1%. 76 Furthermore, this process allowed a 70% average increase in the surface area of the scaffold. The major drawbacks of the negative salt pattern fabrication technique are involvement of multiple complicated steps and cost intensiveness.…”
Section: Advantages and Disadvantages Of Various Scaffold Fabrication...mentioning
confidence: 99%
“…100,101 Ding et al proposed some corresponding countermeasures. The team has fabricated a new type of Mg alloy powder with smooth Table 4.…”
mentioning
confidence: 99%